Perkawinan Beda Agama dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Ai Nur Hasanah; Sani Somantri; Vindi Vindriani (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Interfaith marriage is a legal and social issue that continues to develop within Indonesia’s pluralistic society. This study aims to analyze the regulation of interfaith marriage under Indonesian law, its legal status and validity based on Law Number 1 of 1974 concerning Marriage, as well as its social and legal impacts. The research method used is normative juridical with statutory and literature approaches. The results show that Indonesian marriage law adopts a religious approach, in which the validity of marriage is determined by the respective religious laws of the parties as stipulated in Article 2, paragraph (1) of the Marriage Law. However, the absence of specific regulations regarding interfaith marriage has led to differing interpretations and practices within society. Interfaith marriage also gives rise to legal issues related to marital status, inheritance rights, and civil administration, as well as social impacts such as family conflict and social pressure. From a religious perspective, most religions in Indonesia generally require religious similarity in marriage. Therefore, clearer legal certainty is needed so that the implementation of interfaith marriage can proceed in accordance with the law, religious norms, and the values of tolerance in society.   Keywords: Interfaith Marriage, Marriage Law, Religious Law, Legal Pluralism